Enhancing Bioremediation Potential of Pseudomonas putida by Developing Its Acid Stress Tolerance With Glutamate Decarboxylase Dependent System and Global Regulator of Extreme Radiation Resistance - Zhou, Zikang; Liu, Yuping; Zanaroli, Giulio; Wang, Zhiqiang; Xu, Ping; Tang, Hongzhi (Frontiers in Microbiology, 2019)
The extensive use of acids in a variety of manufacturing industries results in the increase of discharged acidic waste stream into the environment. Such co-pollution of acids and other organic pollutants limits the biodegradation capability of neutrophilic degraders. With high-throughput genetic techniques, we aim to improve the acid tolerance of a pollutant-degrading bacterium, Pseudomonas putida S16 by genetically engineering it with the glutamate decarboxylase (GAD)-dependent system and the global regulator (IrrE) of extreme radiation resistance. The engineered strains holding either GAD system or irrE regulator could grow under pH 4.5, compared to the wild type. They could also degrade over 90% of a selected pollutant (benzoate or nicotine) under pH 5.0 in 48 h, while no biodegradation was detected with the wild type under the same conditions. We conclude that acid stress tolerance by the possession of the GAD system or IrrE regulator in pollutant-degrading bacteria would be a promising approach to enhance their viability and biodegrading activities in bioremediation of acidic wastes.